Performance of System of Wheat Intensification (SWI) and conventional wheat sowing under North Eastern Plain Zone of India - Kumar, Anil; Raj, Rishi; Dhar, Shiva; Pandey, U.C. (Annals of Agricultural Research, 2016)
A field experiment was conducted during the rabi seasons of 2011-12 and 2012-13 at Regional StationIndian Agricultural Research Institute, Pusa, Samastipur, Bihar. System of wheat intensification(SWI) with different plant geometry was compared with conventional line sowing method of wheatunder sandy loam soil. Seed treatment comprises of treated and untreated seed were allocated inmain plot whereas three plant geometry of SWI (10 × 10, 15 × 15 and 20 × 20 cm) and one conventionalline sowing at 22.5 cm were allocated in sub-plot under split plot design with three replications.Treated seed gave relatively higher effective tillers, number of grains and 1000-grain weight ofwheat as compared to untreated seed. SWI at 10 cm × 10 cm recorded significantly higher effectivetillers (345.7 and 405.8 m–2) as compared to SWI at 15 cm × 15 cm or 20 cm × 20 cm spacing duringboth the years. SWI at 10 cm × 10 cm spacing recorded significantly higher grain yield (6.60 and 5.14t ha–1) during 2011-12 and 2012-13, respectively over other treatments. Irrigation water productivitywas highest in SWI method with 10 cm × 10 cm spacing (27.50 and 21.42 kg ha.mm–1) as comparedto conventional line sowing (20.2 and 15. 8 kg ha.mm–1) in 2011-12 and 2012-13, respectively. Thus,there was water saving of 17.3 and 17.8% during 2011-12 and 2012-13, respectively in SWI methodof wheat sowing as compared to conventional line sowing.